2019
DOI: 10.17721/fujcv7i2p9-19
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Association of Dyes with Surfactants in Aqueous Solutions: Spectrophotometry and Computer Simulation

Abstract: The association of cationic dye (pinacyanol, PC) with anionic dyes (ethyleosin, EE, or rhodamine 200 C, R200C), and also the interaction “dye+surfactant” has been investigated in aqueous solutions by visible spectroscopy and computer simulation. Cetylpyridinium bromide (CPB), sodium dodecylsulfate (SDS) and triton X-100 (TX) were used as cationic, anionic and non-ionic surfactants respectively. The formation of “dye+surfactant” associates takes place at low dye concentrations (≥10‑6 M) and concentrations of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Association as a result of the manifestation of intermolecular interactions is accompanied by an increase or decrease in light absorption and changes in spectral bands. For many years, the formation of stable stoichiometric associations between oppositely charged dye ions has been experimentally proven [1][2][3][4][5][6][7][8][9] even at low (1•10 -6 -1•10 -5 mol/L) concentrations. It is shown that "non-Coulomb" interactions are essential in the processes of cation-anion association of dyes or other polyatomic (organic) particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association as a result of the manifestation of intermolecular interactions is accompanied by an increase or decrease in light absorption and changes in spectral bands. For many years, the formation of stable stoichiometric associations between oppositely charged dye ions has been experimentally proven [1][2][3][4][5][6][7][8][9] even at low (1•10 -6 -1•10 -5 mol/L) concentrations. It is shown that "non-Coulomb" interactions are essential in the processes of cation-anion association of dyes or other polyatomic (organic) particles.…”
Section: Introductionmentioning
confidence: 99%
“…Absorption spectra in the system "RB + TFB". Concentrations, mol/L, of RB: 1.07•10 -5 (1…7); of TFB: 0 (1), 1.01•10 -6 (2), 2.02•10 -6 (3), 5.04•10 -6 (4), 6.55•10 -6 (5), 8.06•10 -6 (6), 1.41•10 -5(7). The comparison solution is water.…”
mentioning
confidence: 99%